Competence based Educational Metadata for supporting lifelong competence development programmes - Sampson, Demetrios; Fytros, D. (2008)
In the context of the emerging paradigm of lifelong learning, competence-based learning is gradually attracting the attention of the Technology-Enhanced learning community, since it appears to meet the training expectations of both individuals and organisations. On the other hand, the paradigm of Learning Objects retains, to a large extent, its initial anticipations and, supported by Educational Metadata, it is still influencing Technology-Enhanced learning system design. Nevertheless, the IEEE LOM Specification does not directly support the description of learning resources in terms of their relevance to competence-based learning programmes. In this paper we target addressing this problem, that is, we identify and study the main issues related to the competencerelevant characteristics of learning resources and propose an IEEE LOM Competence Application Profile that can be used for tagging educational resources in a competence-meaningful manner. © 2008 IEEE.